The Effect of CaO on the Recovery of Fe and Ni in a Vacuum Carbothermal Reduction of Garnierite - wang, qiang; Qu, Tao; Shi, Lei; Luo, Ming-yang; Yang, Bin; Dai, Yong-nian (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The effects of adding CaO during a vacuum carbothermal reduction on Fe and Ni recovery yields were examined. In addition, magnetic separation was investigated. Experiments were conducted under pressures ranging from 10 to 50 Pa with different proportions of CaO at different temperatures. The results indicated that at1723 K, the mass ratio of ore/C was 100:65.5; when the amount of CaO was 22.64% (the mole ratio of CaO/Si was 1:1), the recovery of Fe and Ni reached 84.33% and 97.00% in the vacuum carbothermal reduction-magnetic separation process, and the enrichment ratios of Fe and Ni were maximized, reaching 6.32 and 6.72, respectively. In addition, the recovery of Mg in the reduction process reached 99.35%. An analysis of the experimental results also indicated that the addition of CaO could cause the Fe-Si alloy to transform into the Fe-Ni alloy in the nickel-rich residue, which increased the content of Fe-Ni in the magnetic separation material from 13.34% to 73.17%. In addition, the concentration in reduced ore of Si from 45.43% increased to 83.68%, which could reduce the evaporation of Si in the form of SiO at high temperatures. If Si volatilized in the form of SiO during the condensation process, SiO would disproportionate to form Si and SiO2 contaminated condensed magnesium. In summary, the valuable metals in the minerals were comprehensively utilized with the addition of CaO.